Gender Features and Clinical and Prognostic Significance of Neurogenic and Allergic Inflammation Markers in Children with Bronchial Asthma - S.M. Nedelska; O.Yu. Akulova; I.V. Solodova; V.I. Mazur (Zaslavsky O.Yu., 2014)
The article analyzes the gender and clinical and prognostic significance of substance P (subst. P), vasoactive intestinal peptide (VIP) as a markers of neurogenic inflammation and interleukins (IL) 2, 4, 5 and interferon-gamma (IFN-gamma) as markers of allergic inflammation in 34 children with bronchial asthma (BA) aged 10-17 years. The concentration of these markers was determined in blood serum by ELISA twice - in uncontrolled and controlled course of BA. It is proved that the levels of neuropeptide Subst. P and IL-2, IL-4, IFN-gamma had no gender differences and did not reflect the degree of BA control. Analysis of VIP and IL-5 levels revealed a gender dependence of their fluctuations: VIP level was statistically lower, and IL-5 level - higher in boys with uncontrolled BA forms as compared to healthy boys. It can be assumed that the tendency to BA and a higher incidence of BA in boys is associated with reduced VIP levels as a bronchodilator and increased levels of IL-5 as interleukin of allergic inflammation. Upon reaching control over BA course, there was observed an increase in VIP level and decrease in IL-5 level to levels of appropriate indicators in healthy children, regardless of the duration of the disease. Determination of VIP and IL-5 levels can be used as diagnostic markers for efficacy of treatment being carried out and the degree of BA course controllability.